Non-alcoholic fatty liver disease in type 1 diabetes: Prevalence and pathophysiology - Memaj, Plator; Jornayvaz, François R. (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most frequent chronic liver disease in the general population with a global prevalence of 25 %. It is often associated with metabolic syndrome and type 2 diabetes, as insulin resistance and hyperinsulinemia are known to be favoring factors. Recent studies have described growing incidence of NAFLD in type 1 diabetes (T1D) as well. Although increasing prevalence of metabolic syndrome in these patients seems to explain part of this increase in NAFLD, other underlying mechanisms may participate in the emergence of NAFLD. Notably, some genetic factors are more associated with fatty liver disease, but their prevalence in T1D has not been evaluated. Moreover, oxidative stress, poor glucose control and long-lasting hyperglycemia, as well as exogenous insulin administration play an important role in intrahepatic fat homeostasis. The main differential diagnosis of NAFLD in T1D is glycogenic hepatopathy, which needs to be considered mostly in T1D patients with poor glycemic control. This article aims to review the prevalence and pathophysiology of NAFLD in T1D and open perspectives for clinicians taking care of T1D patients with potential hepatopathy.